The effect of an excessive amount of carbon nanotubes on the properties of zinc oxide-carbon nanotube nanocomposites - Guler, Omer (Walter de Gruyter Gmbh, 2016)
The effect of the amount of carbon nanotubes on the electrical and optical properties of carbon nanotube (CNT)-zinc oxide nanocomposites was investigated. In this study, carbon nanotubes were prepared by chemical vapor deposition in a fluidized reactor. The diameters and lengths of the carbon nanotubes that were synthesized were determined by high-resolution transmission electron microscopy to be 20-30 nm and a few micrometers, respectively. Then, CNTs were added to commercial zinc oxide powder to prepare the nanocomposite. The structural, optical, and electrical properties of the samples were characterized by various techniques, such as scanning electron microscopy (SEM), UV-vis absorption, and electrical transport measurements. The room temperature conductivity s25 values of the undoped ZnO and ZnO doped with 0.1% CNTs, 0.2% CNTs, and 5% CNTs were found to be 6.55 x 10(-5), 5.46 x 10(-4), 1.23 x 10(-3), and 2.83 x 10(-2) S/cm, respectively. The optical band gaps of the composites were determined by the Kubelka-Munk theory based on the analysis of diffuse reflectance. The results that were obtained indicated that the electrical and optical properties of ZnO semiconductors can be improved by the incorporation of CNTs. However, the ZnO lost some of its distinctive properties when excess amounts of CNTs were used in the ZnO-CNT composites.
Keywords: carbon nanotubes; nanocomposite; optical properties; ZnO